Monitoring of printed materials and information stands of an educational campaign to increase bean consumption. - Dumani, Marcela (2004)
The results of monitoring the maineducational materials and some interactive activities carriedout during implementation of an educational Campaign toincrease bean consumption are presented in this article. Thestudy included the follow-up on a recipe book, two differentbrochures, and promotional stands located in supermarkets.The Campaign’s materials and activities were made andplanned taking into account the criteria of the peopleparticipating in the study’s initial assessment. In order toassess the contribution of the above mentioned materials andeducational activities to the Campaign, opinions about themwere obtained from the target population. This was alsohelpful to determine their usefulness for other similareducational campaigns or programs to be implemented in thefuture. The recipe book “De todo con Frijoles” was animportant resource for the Campaign. This material waswidely accepted by all mothers. Monitoring the brochuresmade it possible to confirm that mothers highly appreciateinformation received as printed educational material, and thatthe way such information is illustrated and presented isimportant to get people’s interest. Interactive activities areimportant in educational campaigns, because they facilitatedirect contact with the population, allow respondingquestions that might arise, and help obtain additionalknowledge about people’s perception with regards to the foodbeing promoted. Following up on these activities made itpossible to introduce the necessary changes as the Campaignadvanced, which helped to meet the objectives.